การทดสอบความเที่ยงตรงและเชื่อถือได้ของแบบวัดกลวิธีการเผชิญความเครียดเชิงรุก ฉบับภาษาไทย - อรพรรณ ตาทา (จุฬาลงกรณ์มหาวิทยาลัย, 2012)
The Proactive Coping Inventory (PCI), a research instrument, which takes a multidimensional approach to and positive facet of coping that aims for self-regulatory goal attainment and personal growth rather than focuses on self-regulatory threat appraisal. At this moment, PCI has not been officially developed into Thai version. The objective of this study is to develop and test the validity and reliability of The Proactive Coping Inventory: Thai Version for use as a multidimensional research instrument in Thai society. It is the descriptive study design by translating the psychometric instrument and assessing its validity and reliability. Study subjects were Chulalongkorn University undergraduate students aged 18 years, in 1st semester, academic year 2012, recruited purposively to answer 1) personal information questionnaire, and 2) the Proactive Coping Inventory (Greenglass, Schwarzer, and Taubert (1999)): Thai Version, translated from original English version, where Content Validity Index calculated after 5 experts reviewed. Reliability tested data collected data of Internal Consistency - Cronbach’s Alpha method.The study finds that The Proactive Coping Inventory: Thai Version, validity and reliability assessed, internal consistency method, Pearson s product moment correlation results Cronbach’s Alpha between 0.70 – 0.81. It is then concluded that The Proactive Coping Inventory: Thai Version with 7 dimensions (55 items), possess good reliability and validity, suitable for use as multidimensional research instrument in Thai society.